Dampak Pembelajaran dengan Pendekatan Hands on and Minds on terhadap Self Efficacy Matematis Siswa - Rizqi Saputra, Muhammad; Kurniawati, Annisa Dwi (FKIP Universitas Islam Jember, 2024)
This research is a literature review that examines the literature related to the effectiveness of the Hands on and Minds on learning approach on students' self efficacy. Data collection uses the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) method. A total of 20 articles were obtained as qualitative synthesis review materials. This research shows that Hands on and Minds on learning is effective in increasing students' mathematical self-efficacy. However, in terms of learning methods, students generally prefer contextualized Hands on and Minds on learning. The Hands on and Minds on learning model is also effective in improving students' mathematical soft skills, namely computational thinking and systematic thinking.